2020
DOI: 10.21203/rs.3.rs-56012/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Personality, Alexithymia and Work Engagement on Burnout among Village Doctors in China: A Cross-sectional Study

Abstract: Background: In China, grass-roots village doctors, as the gatekeepers of rural residents' health, play an important role in guaranteeing and serving the health level of rural residents. However, the serious burnout and high turnover rate of village doctors threaten the stability of village medical teams. This research evaluated the influence of personality, alexithymia and work engagement on the burnout of village doctors in an in-depth and detailed way, and explored the mediating role of work engagement and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Recruiting medical students with undergraduate or graduate degree to rural areas to be rural doctors might be an important step to fill in the gap. While the fact is, it is difficult to attract new blood to work in rural areas due to identity recognition, career development and low income [8] . Therefore, for most rural doctors with lower education level, apart from routine in-service trainings, instant training that had good feasibility and accessibility and was not subject to venue and time constraint needs to be enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruiting medical students with undergraduate or graduate degree to rural areas to be rural doctors might be an important step to fill in the gap. While the fact is, it is difficult to attract new blood to work in rural areas due to identity recognition, career development and low income [8] . Therefore, for most rural doctors with lower education level, apart from routine in-service trainings, instant training that had good feasibility and accessibility and was not subject to venue and time constraint needs to be enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 62.6% of Chinese rural doctors had contacted with suspected pulmonary TB patients [8] . Although rural doctors are front-line healthcare providers in rural areas and play a crucial responsibility in TB case referral and management, their knowledge on TB control is relatively poor due to lacking sufficient practitioner training [5] , [7] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Recruiting medical students with undergraduate or graduate degree to rural areas to be a village doctors might be an important step to ll in the gap. While the fact is, it is di cult to attract new blood to work in rural areas due to identity recognition, career development and low income [8]. Therefore, for most village doctors with lower education level, apart from routine inservice trainings, instant training that had good feasibility and accessibility and was not subjects to venue and time constraint needs to be enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 62.6% of Chinese village doctors had contact with suspected pulmonary TB patients [8]. Although village doctors are front-line healthcare providers in rural areas and play a crucial responsibility in TB case referral and management, their knowledge and awareness on TB control is relatively poor due to lacking su cient training during work [5,7,9].…”
Section: Introductionmentioning
confidence: 99%